Inducción de mutaciones de color de semilla con metanosulfonato de etilo en algunas variedades de frijol común - Guerra Chomón, J.C.; Moh, C.C; Alan, J.J. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
Certain been varieties possessing characteristics of favorable yield and disease tolerance frequently are not used as cultivars due to the differential preference for certain seed-coat colors among consumers. Changes in the seed-coat color can be induced through the use of mutagenic agents. Germinating seeds of several bean varieties, ´H-182-N´, ´51135-N-1, ´51135-N-2´, ´51052´ with black seed-coat, and ´Chepe´and ´Col-1-63A´ with red seed-coat were treated with ethyl methanesulfonate. Seed-coat color mutants were isolated in four of the six bean varieties in the M2 selfed progeny test. The mutants obtained were white, bayo (from yellowish brown to deep brown), and black with white spots (mosaic). The mutated characters are recessive and inherited in a simple mendelian ratio. The white seed-coat color mutants are due to a genetic change of the dominant pigmentation factor, P, to its recessive form, p.